THE RELATIONSHIP OF THE IMPLEMENTATION OF MOTHER’S LOVE CARE WITH THE LENGTH OF LABOR IN THE 1ST AND 2ND STAGES AT THE CIBADAK HEALTH CENTER - Lesmanawati, Lesmanawati; Umairo, Gusrida (HEARTY, 2024)
Background: Childbirth is a physiological process, where the products of conception (fetus and placenta) are expelled which can live outside the womb, starting with uterine contractions, effacement and opening of the cervix, birth of the baby and placenta through the birth canal or through another route (abdomen), with or without assistance. help. When dealing with a mother in labor, medical personnel are needed who can embrace the mother during the birthing period, so having loving maternal care is important in dealing with a mother in labor. Purpose of writing: To find out how the implementation of maternal care is related to the duration of the first and second stages of labor at the Cibadak Community Health Center. Research methods: The research used is analytical with a cross sectional approach, the research sample is 40 respondents, then testing will be carried out using paired tests and independent sample T tests. Research Results: The results of this research show There is a relationship between the implementation of maternal care and the length of labor in the first and second stages of labor at the Cibadak Community Health Center with a p value of 0.00 0<0.005. Conclusions and Suggestions: The application of loving maternal care to the length of the first and second stages of labor for those who apply and those who do not apply it have different average values because those who apply maternal loving care well will have a faster duration of first and second stages of labor.